2021
DOI: 10.1371/journal.pbio.3001420
|View full text |Cite
|
Sign up to set email alerts
|

Corollary discharge enables proprioception from lateral line sensory feedback

Abstract: Animals modulate sensory processing in concert with motor actions. Parallel copies of motor signals, called corollary discharge (CD), prepare the nervous system to process the mixture of externally and self-generated (reafferent) feedback that arises during locomotion. Commonly, CD in the peripheral nervous system cancels reafference to protect sensors and the central nervous system from being fatigued and overwhelmed by self-generated feedback. However, cancellation also limits the feedback that contributes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 82 publications
(244 reference statements)
0
7
0
Order By: Relevance
“…One possible explanation for swimming adaptation following loss of flow sensing and vision is that hatchlings combine sensory information from both modalities to evaluate motion levels. The lateral line conveys signals not only about external flow but also motion generated by swimming [54], providing a gross readout of transport. Given that zebrafish can intensify swimming under restraint in virtual reality [55], we next tested the hypothesis hatchlings swim more vigorously without lateral line or visual sensation.…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation for swimming adaptation following loss of flow sensing and vision is that hatchlings combine sensory information from both modalities to evaluate motion levels. The lateral line conveys signals not only about external flow but also motion generated by swimming [54], providing a gross readout of transport. Given that zebrafish can intensify swimming under restraint in virtual reality [55], we next tested the hypothesis hatchlings swim more vigorously without lateral line or visual sensation.…”
Section: Resultsmentioning
confidence: 99%
“…The lateral line, the swim bladder, and buoyancy Classical work has defined the role of the lateral line 3 , while recent studies have expanded our understanding of this remarkable organ. Functional investigation of the lateral line has demonstrated sophisticated comparisons of expected and observed patterns of flow during swimming [23][24][25][26][27] . Studies of lateral line neuromasts have revealed foundational principles of patterning 28,29 , organogenesis 30,31 , molecular and functional descriptions of hair cells [32][33][34] , and sensitivity to ototoxic compounds 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…The lateral line system appears to provide feedback about the fish's own movement ( Ayali et al, 2009 ). Furthermore, feedback between sequential lateral line neuromasts has been theorized to allow the calculation of body wave parameters such as wave frequency ( Skandalis et al, 2021 ). The body wave parameters encoded by sequential neuromasts could be altered or missing when the lateral line is blocked, resulting in changes in wave frequency as the fish is unable to determine its own movement.…”
Section: Discussionmentioning
confidence: 99%